Silicon carbide and related materials 2019 : selected, peer-reviewed papers from the 18th International Conference on Silicon Carbide and Related Materials 2019 (ICSCRM 2019), September 29 - October 4, 2019, Kyoto, Japan - Yano, Hiroshi; Ohshima, Takeshi; Eto, Kazuma; Harada, Shinsuke; Mitani, Takeshi; Tanaka, Yasunori (Materials science forum ;, 2020)
This volume contains papers from the 18th International Conference on Silicon Carbide and Related Materials 2019 (ICSCRM 2019), held in Kyoto, Japan, from September 29 through October 4, 2019. The collection reflects the results of the last research efforts on properties of silicon carbide and related materials for the goal of their use in power electronics. Presented articles, cover the wide range of topics: crystal growth and wafer manufacturing, characterization and defect engineering, MOS gate stacks and device processing, power devices, and integrated circuits packaging. Silicon Carbide, Crystal Growth, Epitaxial Growth, Thin Films, Layer Growth, Etching, Wafer Machining, Characterization, Measurements, Point Defects, Extended Defects, Quantum Technologies, MOS Gate Stack, Metal-Oxide-Semiconductor Field-Effect Transistor, Bipolar Devices, Junction Field-Effect Transistor, Diodes, Barrier Schottky, Silicon Carbide Power Devices, High-Temperature Reliability, Integrated Circuits Packaging Materials Science, Manufacturing, Electronics.